Inflation in a virtual economy – a real or virtual threat? - Maciejasz-Świątkiewicz, Marta; Musiał, Mateusz (Inflacja w wirtualnej gospodarce – realne czy wirtualne zagrożenie?, 2014)
The aim of the paper is an analysis of the way and circumstances under which inflation can occur in a virtual economy. It is also an attempt to answer the question whether, and in what way virtual inflation may be related to inflation in the real economy. The article is conceptual, because in the present state of statistical data the effects of virtual economies are not carried out, or are generated in a very small number, which makes it impossible to make reliable calculations
Nauki o Finansach = Financial Sciences, 2014, Nr 4 (21), s. 42-51
Keywords: inflation; virtual economy; virtual money; inflacja; wirtualna gospodarka; wirtualny pieniądz